2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--21387
|View full text |Cite
|
Sign up to set email alerts
|

Faculty and Student Perceptions of Online Learning in Engineering Education

Abstract: is professor of learning technologies in the College of Education. She is the Program Coordinator and Graduate Advisor for the Learning Technologies Program. She develops and teaches graduate courses on new media design, production, and research. Her research interests center on educational uses of new media and other emerging technologies, particularly the impact of such technologies on teaching and learning, and the design of new media enriched interactive learning environments for learners at all age levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Moreover, there is a positive correlation between students and faculty in their perception of teaching and learning (Seok et al, 2010). Faculty and students of engineering specialties incurred that theoretical engineering subjects can be taught online, while teaching practical courses online are less effective and should be conducted at engineering labs (Kinney et al, 2012). Similarly, students' and faculty perceptions were marginalized differently in teaching laboratory courses online (Beck and Blumer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, there is a positive correlation between students and faculty in their perception of teaching and learning (Seok et al, 2010). Faculty and students of engineering specialties incurred that theoretical engineering subjects can be taught online, while teaching practical courses online are less effective and should be conducted at engineering labs (Kinney et al, 2012). Similarly, students' and faculty perceptions were marginalized differently in teaching laboratory courses online (Beck and Blumer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this respect, Kinney et al (2012) demonstrated that technical topics are suitable to be effectively taught through online methods, suggesting at that moment that such methods are crucial for the future of online engineering education. On the other hand, the results of the study underlined that engineering lab experiences cannot be delivered online.…”
Section: Introductionmentioning
confidence: 99%
“…Delivering online hands-on laboratory, project-based courses, or computer labs is challenging versus the more traditional face-to-face environment. Faculty feel that teaching "lecture only" online course materials through streaming/recorded video content is most effective, while students feel that online education requires additional time and reduces interaction (Kinney et al 2012) with faculty and peer students. Similarly, Schmidt et al (2013) also suggested that online teaching requires more time than face-to-face teaching.…”
Section: Introductionmentioning
confidence: 99%